Performance enhancement of a novel tandem CZTSe structure based solar cells: A numerical simulation - GUEDDOUDA Mustapha Kamal; Selmane, Naceur (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2023)
This research focuses on addressing the challenges associated with indium-based CuInGaSe (CIGS) solar cells by proposing a novel solar cell structure. The objective is to maintain the benefits of CIGS structures while reducing the use of costly and hazardous elements. The proposed structure involves the addition of a CuZnSnSe (CZTSe) layer to the core configuration (p-CIGS/n-Cds/n-ZnO) and optimizing it to achieve high efficiency. Through optimization of parameters such as layer thickness, doping concentration and band gap while maintaining a reduced CIGS layer thickness. The results demonstrate that adding a CZTSe layer will increase the efficiency of the cell from 25% until 28%, this is while lowering some toxic materials and adding environmentally friendly martials. In continuation of the research, the proposed solar cell structure with the CZTSe double absorber layer demonstrates promising performance enhancements. Building upon this progress, an additional novel feature is introduced by incorporating a rubidium germanium triiodide (RbGeI3) perovskite layer to form a tandem solar cell configuration. The perovskite layer, placed on top of the CZTSe/CIGS double absorber layer, aims to further enhance the efficiency of the solar cell and also holds the potential to achieve efficiencies nearing 40%
option: Microelectronic Engineering